1991
DOI: 10.1002/hep.1840130303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hepatitis B virus, alcohol drinking, cigarette smoking and familial tendency on hepatocellular carcinoma

Abstract: Independent and interactive effects related to the development of hepatocellular carcinoma were assessed using a community-based case-control study for hepatitis B virus, habitual alcohol drinking, cigarette smoking, peanut consumption and history of hepatocellular carcinoma among the immediate family. All 200 male newly diagnosed hepatocellular carcinoma patients were recruited consecutively through the period of study as the case group from two teaching medical centers in northern and southern Taiwan. Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(106 citation statements)
references
References 21 publications
(2 reference statements)
8
95
1
1
Order By: Relevance
“…This result is consistent with those reported previously in China,14 Hong Kong,23 and Taiwan 24. Cigarette smoking and chronic hepatitis B virus carrier status were also reported to act synergistically in the development of hepatocellular carcinoma 25.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with those reported previously in China,14 Hong Kong,23 and Taiwan 24. Cigarette smoking and chronic hepatitis B virus carrier status were also reported to act synergistically in the development of hepatocellular carcinoma 25.…”
Section: Discussionsupporting
confidence: 92%
“…The main risk factors for liver cancer are hepatitis B infection, hepatitis C infection, and chronic hepatitis and cirrhosis due to alcohol and other causes. 51-56 In 2013, of the 818 000 deaths in men and women, 300 000 (37%) were estimated to be due to hepatitis B infection, 343 000 (42%) due to hepatitis C infection, 92 000 (11%) due to alcohol abuse, and 83 000 (10%) due to other causes. 1 Hepatitis B vaccination has proven cost-effective in preventing liver cancer due to hepatitis B, and treatment for hepatitis C, although expensive, has recently shown success.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported increased risk (2-fold) in patients with HCV/HBV infections or diabetes mellitus combined with chronic alcohol consumption. Additionally, the synergistic effect between HCV/HBV infection and chronic alcohol abuse has also been reported in other countries where hepatitis infections are more prevalent (4;5). …”
Section: Introductionmentioning
confidence: 60%